RISK MANAGEMENT IN ISLAMIC FINANCIAL INSTITUTIONS: AN ISLAMIC LEGAL APPROACH TO THE PRACTICE OF GHARAR AND MAISIR - Samsulijar (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
Sharia financial institutions (SFIs) face various risks that must be managed carefully and in accordance with sharia principles. Among the main challenges is avoiding the practices of gharar (uncertainty) and maisir (speculation/gambling), both of which are prohibited in Islam. This article aims to analyse the Islamic legal approach to risk management in Islamic financial institutions, with a focus on identifying, mitigating, and preventing gharar and maisir. A qualitative-descriptive approach was used in this study, involving an analysis of Islamic legal literature, fatwas from the DSN-MUI, and the practices of Islamic financial institutions in Indonesia. The findings indicate that the principles of contract clarity, risk-sharing, and Shariah supervision are important instruments for ethical and sustainable Shariah risk management